On the relation between the material welfare and moral training of the industrious classes - Walsh, Richard Hussey (Dublin Statistical Society, 1851)
We live in an age of industrial progress; improvements and inventions in the different arts and sciences, have furnished unprecedented facilities for the production of luxuries and comforts of every kind. Yet side by side with that brilliant picture exists a mass of pauperism, and of persons verging on it, presenting a most unhappy spectacle?rendered still more remarkable by the contrast it affords to the surrounding affluence. This prospect has naturally excited the attention of many, and various explanations of the phenomenon and remedies for the evil have been proposed.
Read January 20th 1851
Keywords: Education; Working classes; Welfare; 314.15